2014
DOI: 10.1093/hmg/ddu197
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue alterations in Fkbp10−/− mice

Abstract: Osteogenesis imperfecta (OI) is an inherited brittle bone disorder characterized by bone fragility and low bone mass. Loss of function mutations in FK506-binding protein 10 (FKBP10), encoding the FKBP65 protein, result in recessive OI and Bruck syndrome, of which the latter is additionally characterized by joint contractures. FKBP65 is thought to act as a collagen chaperone, but it is unknown how loss of FKBP65 affects collagen synthesis and extracellular matrix formation. We evaluated the developmental and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 34 publications
3
55
0
1
Order By: Relevance
“…No colocalization was observed with the Golgi-specific protein GOLGA1 (29), indicating that FKBP10 is not associated with transport processes across the trans-Golgi network to the extracellular space. This suggests that FKBP10 mainly functions as an ER-resident chaperone and/or foldase in phLF, which agrees with previous studies in chondroblasts and embryonic fibroblasts (19,27). As there is evidence that ER stress contributes to IPF pathology (30, 31), we assessed whether FKBP10 is induced by ER .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No colocalization was observed with the Golgi-specific protein GOLGA1 (29), indicating that FKBP10 is not associated with transport processes across the trans-Golgi network to the extracellular space. This suggests that FKBP10 mainly functions as an ER-resident chaperone and/or foldase in phLF, which agrees with previous studies in chondroblasts and embryonic fibroblasts (19,27). As there is evidence that ER stress contributes to IPF pathology (30, 31), we assessed whether FKBP10 is induced by ER .…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in FKBP10 lead to collagen-related disorders such as osteogenesis imperfecta, and studies in the last 4 years have suggested an association of these mutations with attenuated collagen secretion and diminished collagen I cross-linking in dermal fibroblasts and bone (15)(16)(17)(18). A recent study showed that Fkbp10 2/2 mouse embryos are postnatally lethal and display reduced collagen cross-linking in calvarial bone (19).…”
mentioning
confidence: 99%
“…Further studies are required to address the particular details of the interaction between Hsp47 and the SH3 domain of TANGO1. It is interesting to note that null mouse models of Hsp47, FKBP65, Prolyl 3-hydroxylase 1, and cartilage-associated protein show embryonic lethality or disturbances in various tissues (30,(35)(36)(37) and that human mutations in these proteins lead to a phenotype of recessive OI (38).…”
Section: Discussionmentioning
confidence: 99%
“…They result in loss of prolyl-hydroxylation at Pro-986 (27) and, in CypB knock-out mice, defective lysine hydroxylation in bone (28) and tendon (29) collagens. Furthermore, we know that FKBP65, another peptidyl prolyl isomerase and ER chaperone, can regulate the activity of LH2 the predicted telopeptide lysine hydroxylase (12,30,31).…”
Section: Discussionmentioning
confidence: 99%